PENGARUH STRUKTUR MODAL (DER), EARNING PER SHARE (EPS), DAN KEBIJAKAN DIVIDEN (DPR) TERHADAP NILAI PERUSAHAAN SEKTOR BASIC INDUSTRY CHEMICALS YANG TERDAFTAR DI BEI PERIODE 2014 – 2018 - Sitompul, Mario Joseph Valentino; Sisilia, Mariska; Sitompul, Melva Melany; Sihite, Edo Tumpak; Situngkir, Irene Artha Uli; Lombu, Novia Eunike; Chairunnisa, Ulfa (Aksara Public, 2019)
This study discusses to discuss and analyze the capital structure (DER), produce Per Share, and dividend policy on the value of the company in the companies of Basic Industrial Chemicals listed on the Indonesia Stock Exchange for the period 2014-2018. The research method used in this study uses quantitative research methods, the type of research is descriptive quantitative, explanatory nature of research. The population of this study amounted to 66 basic industrial chemical companies with sampling techniques aimed at sampling 14 basic industrial chemical companies that met the criteria. The method of data analysis in this study is multiple linear regression analysis with classical assumption. The results of this study indicate the simultaneous structure of Capital, Earnings Per Share, and Dividend Policy simultaneously and significantly to the Company Value in the Basic and Chemical Industry companies listed on the Indonesia Stock Exchange for the 2014-2018 period with the results of Fcount ≥ Ftable 3.213 ≥ 2 74 and significant 0.028 5 0.05. Partially the Capital Structure and Per Share Income does not affect and is not significant to the Company Value while the Dividend Policy affects positively and significantly on the Firm Value. The results of the analysis of the determination coefficient obtained adjusted R2 values ​​indicate variations in the variable value of the company that can be determined by variations in the variable capital structure, earnings per share and dividend policy of 8.8% while 91.2% is produced by variations in other variables.